Vanadium Exposure in Early Pregnancy and Increased Risk of Gestational Diabetes Mellitus. (7th June 2021) - Cao, Xiyu; Lin, Lixia; Wu, Meng; Xiao, Daxiang; Tu, Menghan; Yang, Nianhong; Zhang, Guofu
Abstract: Objectives: To investigate the association between blood vanadium (V) concentrations in early pregnancy and blood lipid profiles and their implications on gestational diabetes mellitus (GDM). Methods: We performed a prospective study of 2416 pregnant women from the Tongji Maternal and Child Health Cohort (TMCHC). Demographic characteristics and dietary intake were obtained by questionnaire, and an oral glucose tolerance test (OGTT) was conducted at 24–28 gestational weeks to diagnose GDM. V concentrations and lipid levels were determined by analysis of blood samples, which were collected before 20 gestational weeks, with the use of inductively coupled plasma mass spectrometry (ICP-MS) and commercial assay kits. Multiple linear regression and Logistic regression were used in our analysis. Results: The median (inter quartile range) value of V concentrations of all pregnant women was 0.19 (0.24, 0.32) μg/L. After adjusting for demographic and dietary factors, low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and total cholesterol (TC) were correlated positively with blood concentrations of V ( p for trend = 0.002 for LDL-C, p for trend = 0.006 for TG and p for trend = 0.003 for TC) while there was a significant negative correlation between high-density lipoprotein cholesterol (HDL-C) and V concentrations ( p for trend < 0.001). In addition, V concentrations were significantly higher in women with GDM than those without GDM (median value: 0.26μg/L vs. 0.24μg/L,  p < 0.001). After adjustment for potential confounders, for each one natural logarithmic unit increase in V concentrations, there was 42% [adjusted odds ratio (OR) = 1.42; 95% confidence interval (CI): 1.14, 1.77] increase in the risk of GDM. Women in the highest quartile for V had a 2.24-fold (95% CI: 1.43, 3.52) higher risk of GDM compared with women in the lowest quartile ( p for trend = 0.002). Conclusions: To our knowledge, this is the first research of associations between blood V levels during pregnancy and blood lipid profiles or GDM. Our study suggests that pregnant women with higher V exposure levels may have higher risks of dyslipidemia and GDM, either evaluated with or without adjustment of demographic information, dietary factors or other common trace elements' concentrations. Funding Sources: Received from the National Program on Basic Research Project of China (NO.2013FY114200) for Nianhong Yang.